2019
DOI: 10.3390/ijms21010106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gangliosides on Spermatozoa, Oocytes, and Preimplantation Embryos

Abstract: Gangliosides are sialic acid-containing glycosphingolipids, which are the most abundant family of glycolipids in eukaryotes. Gangliosides have been suggested to be important lipid molecules required for the control of cellular procedures, such as cell differentiation, proliferation, and signaling. GD1a is expressed in interstitial cells during ovarian maturation in mice and exogenous GD1a is important to oocyte maturation, monospermic fertilization, and embryonic development. In this context, GM1 is known to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 113 publications
(124 reference statements)
2
19
0
Order By: Relevance
“…The HEXA gene in our study was also significantly higher expressed in porcine blastocysts which corresponds to upregulation of a substrate specific cofactor GM2A. Most of publications describe GM1, GM3 and GD1a gangliosides as important factors involved in the EGFR (epidermal growth factor receptor) signaling pathway [28]. In porcine embryos, exogenous GD1a supported maturation and blastocyst formation in vitro [29].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The HEXA gene in our study was also significantly higher expressed in porcine blastocysts which corresponds to upregulation of a substrate specific cofactor GM2A. Most of publications describe GM1, GM3 and GD1a gangliosides as important factors involved in the EGFR (epidermal growth factor receptor) signaling pathway [28]. In porcine embryos, exogenous GD1a supported maturation and blastocyst formation in vitro [29].…”
Section: Discussionsupporting
confidence: 62%
“…GM2 Activator, also known as SAP3 (Shingolipid Activator Protein 3), coded by the GM2A gene, is one of the components of the B-hexosaminidaseA (HEXA) complex necessary for the enzymatic processing of gangliosides, which are sialic acid-containing acidic glycosphingolipids. Gangliosides found in animal plasma membranes exhibit cell-type specificity and are implicated in various cellular functions, differentiation, signal transduction and immunity [27,28]. The HEXA gene in our study was also significantly higher expressed in porcine blastocysts which corresponds to upregulation of a substrate specific cofactor GM2A.…”
Section: Discussionsupporting
confidence: 56%
“…Because the reduction of average litter size was obvious in F3, our further analysis focused on the comparison between F3 and 3M groups. It has been shown that decrease in litter size could result from dysfunctional uteri or decreasing embryo number [20,21], and most problems during embryonic development are associated with placentation defects [22]. In examining day 12 (D12) pregnant mice, F3 mice were revealed to have abnormal uteri compared with 3M mice (Fig.…”
Section: Pregnancy Outcome and Placental Developmentmentioning
confidence: 99%
“…This effect of EBN might be due to its potential bioactive components; the nutritional composition of EBN is protein, carbohydrate, ash, and lipids (Ma & Liu, 2012), while sialic acid is the major carbohydrate component found in EBN (Daud et al, 2019). Sialic acid-containing gangliosides have been demonstrated to efficiently protect oocytes and embryos from ROS produced injury, which is one of the major mechanisms of Cd toxicity (Kim et al, 2020;Wang et al, 2019).…”
Section: Histopathological Examinationmentioning
confidence: 99%